Optimal design of minimal footprint high frequency transformer - Banumathy Jeyapradha Ravichandran (Faculty of Technical Sciences in Cacak, 2021)
Transformer design procedure may vary essentially in respect of the transformer type and its operating frequency (ranging between 50/60 Hz and a few megahertz). This paper presents a simple and straightforward method based on the optimal choice of core geometry of a high frequency transformer (HFT) used in Solid State Transformer (SST) applications. The core of SST is the HFT which largely influences its size and overall performance. The proposed design procedure for HFT focuses on optimizing the core geometry coefficient (in cm5) with a constraint inflicted on loss density. The core geometry coefficient has direct impact on the regulation and copper loss and the procedure results in a robust overall design with minimal footprint. Also, the procedure intends to bring all the operating parameters like regulation, losses and temperature rise within permissible limits while retaining desired efficiency. Thus an energy-efficient design is achieved with minimal footprint. The optimization procedure is implemented using recently developed Moth-flame Optimization (MFO) algorithm. The results of the MFO algorithm are compared with the wellestablished PSO technique. An experimental prototype is built to validate the findings.